Full-width postlaminar optic nerve tumor invasion of retinoblastoma as risk-factor for leptomeningeal spread of retinoblastoma. A case report and review of the literature. (2nd January 2020) - de Jong, Marcus C.; van der Valk, Paul; Jansen, Robin W.; Abbink, Floor; Bosscha, Machteld; Castelijns, Jonas A.; Moll, Annette C.; de Graaf, Pim
ABSTRACT: We present a 6-year-old boy with unilateral retinoblastoma of the left eye. MRI showed an intraocular tumor that extended into the optic nerve beyond the lamina cribrosa. The affected eye was enucleated and the optic nerve resection margin proved to be free. Following protocol, this patient received six courses of adjuvant systemic chemotherapy. Unfortunately, after 5 months this patient returned with the leptomeningeal spread of the tumor and died quickly thereafter. Histopathologic analysis of the enucleated eye and distal optic nerve revealed that the postlaminar tumor cells occupied the entire width of the optic nerve, extending all the way up to the pia mater, whereas, more often the tumor invasion is restricted to the center of the optic nerve. This was also visible on the MR images where contrast enhancement occupied the entire nerve width. A resection margin with tumor cells is recognized as a risk factor for metastasis, but perhaps the proximity of tumor cells to the leptomeninges should also be judged with caution as a potential increased risk for metastatic spread.